Unemployment protection for informal workers in Latin America and the Caribbean - Alan Finkelstein Shapiro; Miguel Sarzosa (Inter-American Development Bank (IDB), 2013)
We use a dynamic stochastic general equilibrium search and matching model with salaried employment and informal self-employment to analyze the implications of introducing universal unemployment protection for informal workers through transfers, which are conditional on participation in training programs. We study how changes in unemployment benefits (UB) for unemployed workers in training programs (training UB), modify labor market outcomes for the unemployed. The model suggests that increasing training UB reduces unprotected unemployment and improves labor market outcomes through higher formal salaried employment and lower informal self-employment. Allowing for idiosyncratic quality in these training programs is key for these results. Higher training UB can also reduce total informal employment through a drastic reduction in the share of informal self-employment, without necessarily causing a large increase in total unemployment. Finally, the model suggests that increasing training UB may increase the volatility of unprotected unemployment. The influence of training programs on formal wage-setting is crucial to explain these results.
hdl:11319/4542
Keywords: E02; E24; E26; 330; Business cycles; informality; labor search